El crimen en la costa Caribe colombiana: Bases para el diseño de una política pública (2012)
Based on panel data for the departments of the Colombian Caribbean coast in the period 1993-2007, the crime rate was estimated using the ordinary least squares method. In this way, it was possible to minimize the econometric problems, which affect most of the research in this field, such as the endogeneity of the explanatory variables, and measurement errors due to the underreporting of crime rates. The estimations allow to conclude that the degree of poverty, measured in terms of the NBI, generates a negative effect on the crime rate; the population density has positive effects for the crimes of homicide, common theft and personal injuries, and negative for vehicle theft and kidnapping; likewise, the schooling rate has a positive impact on common theft and injuries; the efficiency rate of the police, and the departmental GDP per capita is only significant for the crimes of common theft and vehicle theft. The departmental fixed effects show that the specific characteristics of the departments do not explain the differences in crime rates. This research is an empirical contribution to the current debate of the studies on the economics of crime, through a review of the bibliography of criminal investigations that have taken place in the country. Additionally, it raises some questions to develop in a future research agenda